2006
DOI: 10.1097/01.aud.0000215974.74293.b9
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Auditory Steady-State Response Thresholds to Bone-Conduction Stimuli in Young Infants with Normal Hearing

Abstract: Infant bone-conduction ASSR thresholds are very different from those of adults. Overall, these results indicate that low-frequency bone-conduction thresholds worsen and high-frequency bone-conduction thresholds improve with maturation. Bone-conduction ASSR threshold differences between the postterm infants and adults probably are due to skull maturation. Differences between preterm and older infants may be explained both by skull changes and a masking effect of high ambient noise levels in the NICU (and possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 21 publications
10
56
2
3
Order By: Relevance
“…No significant differences were found for ASSR threshold between the temporal bone and mastoid bone oscillator placements. Consistent with our results reported in a previous study (Small & Stapells, 2006), boneconduction ASSR thresholds in preterm infants were significantly lower (i.e., better) at 500 and 1000 Hz compared with 2000 and 4000 Hz.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…No significant differences were found for ASSR threshold between the temporal bone and mastoid bone oscillator placements. Consistent with our results reported in a previous study (Small & Stapells, 2006), boneconduction ASSR thresholds in preterm infants were significantly lower (i.e., better) at 500 and 1000 Hz compared with 2000 and 4000 Hz.…”
Section: Resultssupporting
confidence: 83%
“…Bone-conduction ASSR amplitudes at 30 dB HL for 500 and 1000 Hz and at 40 dB HL for 2000 and 4000 Hz were compared across frequency and coupling condition. A greater intensity was selected for 2000 and 4000 Hz than for 500 and 1000 Hz to compensate for poorer thresholds (approximately 10 dB) at these higher frequencies (Small & Stapells, 2006). Statistical analyses • A 2-way repeated-measures ANOVA was performed comparing ASSR thresholds for 10 infants at 500, 1000, 2000 and 4000 Hz between coupling methods (elastic-band and hand-held).…”
Section: Ear and Hearing / February 2007mentioning
confidence: 99%
“…For infants, mean ASSR thresholds were 13 to 15 dB poorer for ASSRs recorded in the contralateral EEG channel compared with those in the ipsilateral EEG channel; the channel effect was statistically significant [F(1,10) ϭ 34.468, p ϭ 0.0002]. There was a significant effect of frequency [F(3,30) ϭ 5.046, p ϭ 0.006], similar to results reported in our previous studies (Small & Stapells, 2006; submitted for publication); however, no significant interaction between EEG channel and frequency [F(3,30) ϭ 0.759, p ϭ 0.526] was found. For adults, there was no difference between mean ASSR thresholds for responses recorded in the contralateral or ipsilateral EEG channels [F(1,14) ϭ 0.028, p ϭ 0.869].…”
Section: Assr Thresholdsupporting
confidence: 80%
“…Our recent studies were the first to estimate bone-conduction thresholds in infants using multiple ASSRs Small & Stapells, 2006). The results of these studies showed that it is possible to record bone-conduction ASSRs to multiple stimuli in pre-and postterm infants with normal hearing and revealed differences in bone-conduction thresholds between two infant groups compared with adults.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation